The effectiveness of status conflict in the conservation of Sultanahmet urban archaeological site - Ornek, Elif (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2023)
Protecting and transferring the historical, cultural, and natural environment to future generations are recognised as one of the primary responsibilities of humanity. The immediate result of such a responsibility is to replace individual efforts and initiatives with joint ownership of the heritage and gradually with systems and policies with national and international dimensions and common language and concepts. The policies countries pursue in this direction are one of the critical factors determining the level of development in conservation policies. On the other hand, cultural and natural assets and historical environments are considered as a record that sheds light on the urban and architectural design, construction techniques, and social life of a certain period, and thus, in a sense, they undertake an instructive task. Therefore, today it is aimed to protect the underground, aboveground or underwater values, called cultural heritage, as a component of local and universal culture and a record of civilisation with the help of the laws, international agreements, conventions, and regulations. However, behaviours and policies that are no based on scientific data and are not objective and universal cause destruction because they fail to exhibit a comprehensive approach that can integrate cultural heritage into social, economic, social, and cultural life. They also create interruptions and result in indefinite periods in the maintenance of urban identity and urban culture. The research area of this article is in the Historical Peninsula of Istanbul, where all the changes in the conservation policies of Turkey can be observed. This study examined the different conservation statuses attributed to the area over time and the spatial outcomes of these statuses. As a result, this study aims to discuss, despite all the laws, international agreements, and conflicts of status, and why we have not achieved the desired success in the conservation of urban archaeological conservation sites.Cite this article as: ornek E. The effectiveness of status conflict in the conservation of Sultanahmet urban archaeological site. Megaron 2023;18(2):218-230.
Keywords: Key Historical Peninsula; urban conservation area; urban archaeological conservation site; urban conservation; Architecture